The impact of sleep disorders on brain network connectivity in postpartum women: a functional near-infrared spectroscopy-based study - Chen, Xia; Zhao, Shanguang; Chen, Danni; Zhang, Dan (Frontiers in Neurology, 2024)
Sleep disorder is an important risk factor for postpartum depression. Although previous research has explored brain activity in postpartum depression, it has not fully revealed how insomnia affect mood by altering interactions between brain regions. This study aim to investigate the relationship between insomnia and depressive status in postpartum women, utilizing functional near-infrared spectroscopy (fNIRS) to explore brain network topological properties. Among 143 postpartum women, 40 were diagnosed with insomnia and 103 without. The results indicated that the Edinburgh Postnatal Depression Scale (EPDS) scores were significantly higher in the insomnia group compared to the control group. Compared with the control group, the insomnia group showed significantly increased connection strength of triangularis Broca's between middle and superior temporal gyrus and left between right dorsolateral prefrontal cortex (p < 0.001). Brain network topological analysis revealed that the small-world properties, clustering coefficient (p = 0.009), and local efficiency (p = 0.009) were significantly lower in the insomnia group compared to the control group. Notably, the local efficiency and clustering coefficient of the left temporal pole were significantly reduced and negatively correlated with EPDS scores. These findings elucidate how insomnia may exacerbate postpartum depression through changes in brain network properties. While the observed alterations in connectivity suggest a correlation, causation cannot be definitively established. Improving sleep quality remains a promising intervention, but further research is needed to clarify causal links and therapeutic targets.